Porosity-enhanced solar powered hydrogen generation in GaN photoelectrodes - Yaonan Hou (Applied Physics Letters, 2017)
Two types of GaN based photoelectrodes using either horizontally aligned or vertically aligned nanopores have been fabricated by means of using an electrochemical etching approach. The photoelectrodes based on such nanostructures have demonstrated an up to 5-fold enhancement in applied bias photon-to-current efficiency and incident photon-to-current efficiency in comparison with their planar counterpart, leading to a high Faradaic conversion efficiency which approaches 1. The GaN photoelectrodes with these nanopores also show excellent chemical stability in HBr solution as an electrolyte. The results presented reveal that the gas diffusion in the nanopores plays an important role in water splitting processes, which should be taken into account when designing a GaN photoelectrode with a nanopore structure.